Exploring the Market Demand for Local Organic Rice in Malaysia - Othman, Zakirah; Samah, Rozana; Musa, Suria (CENTRAL ASIA AND THE CAUCASUS, 2021)
The global organic rice market is in a growing trend. This situation is also found in Malaysia, where the demand for organic rice also on the rise. The increase in demand for organic rice is due to the growth of Malaysian's per capita income that has empowered consumers to have more purchasing power. Health consciousness and demand for more nutritional value food are also the reason for organic rice demand. Besides, the factors such as food safety concerns and environmental concern are also the factors that affect consumers' demand for organic food products in this era. Organic rice can be defined as rice produced from practice management without chemicals, especially in fertilization and pest control. Thus, this study determined the demand status of local organic rice in Malaysia, and the factors influence the demand. Market demand research is critical because it will describe the consumer demand for a given product and the factors that influence it. As market demand increases, so does the price. Thus, this will promote and motivate the farmers towards sustainable or ecologically friendly agriculture. Primary data were collected by using a questionnaire through a survey in Malaysia. The data obtained were analyzed using the basic statistical method, which is descriptive statistics. Descriptive analysis was done in the Statistical Package for Social Science (SPSS) application. The results have shown that organic rice demand is positive but still low in terms of quantity. Socio- demographic factors such as age, educational level, income level, and health purpose have been the factors influencing consumer’s demand for local organic rice.